Umar al-Mukhtar ([S.l. : s.n.)
Story about the life of Umar al-Mukhtar. His life and his sacrifice in facing with war in order to protect Islam and the right of muslims
VCD format
Keywords: Mukhtar,'Umar, -- 1860?-1931; Motion pictures; War